Finite Element Method Analysis of Compression Fractures on Whole-Spine Models Including the Rib Cage. (5th May 2019) - Nishida, Norihiro; Ohgi, Junji; Jiang, Fei; Ito, Saki; Imajo, Yasuaki; Suzuki, Hidenori; Funaba, Masahiro; Nakashima, Daisuke; Sakai, Takashi; Chen, Xian
Abstract : Spinal compression fractures commonly occur at the thoracolumbar junction. We have previously constructed a 3-dimensional whole-spine model from medical images by using the finite element method (FEM) and then used this model to develop a compression fracture model. However, these models lacked the rib cage. No previous study has used whole-spine models including the rib cage constructed from medical images to analyze compression fractures. Therefore, in this study, we added the rib cage to whole-spine models. We constructed the models, including a normal spine model without the rib cage, a whole-spine model with the rib cage, and whole-spine models with compression fractures, using FEM analysis. Then, we simulated a person falling on the buttocks to perform stress analysis on the models and to examine to what extent the rib cage affects the analysis of compression fractures. The results showed that the intensity of strain and the vertebral body with minimum principle strain differed between the spine model including the rib cage and that excluding the rib cage. The strain on the spine model excluding the rib cage had approximately twice the intensity of the strain on the spine model including the rib cage. Therefore, the rib cage contributed to the stability of the thoracic spine, thus preventing deformation of the upper thoracic spine. However, the presence of the rib cage increased the strain around the site of compression fracture, thus increasing the possibilities of a refracture and fractures of adjacent vertebral bodies. Our study suggests that the analysis using spine models including the rib cage should be considered in future investigations of disorders of the spine and internal fracture fixation. The development of improved models may contribute to the improvement of prognosis and treatment of individual patients with disorders of the spine.